Ephemerides of Visual Binaries of highly eccentric orbits - Elsanhoury, Waleed; H., W. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Ephemerides of binary stars are important information for astronomical observation and research. In this paper, ephemerides of the visual binaries ADS784, ADS13665, A1529, ADS836, ADS 3434, ADS1105 and ADS 3315 have been calculated using a computational algorithm to the successive approximations method. Ephemerides prediction to the visual binary systems of highly eccentric orbits is evaluated up to the year 2021. Comparisons with the observations are in good agreement.